Examination of precipitation variability in southern Greenland. Issue 12 (21st June 2017) - Auger, Jeffrey D.; Birkel, Sean D.; Maasch, Kirk A.; Mayewski, Paul A.; Schuenemann, Keah C.
Abstract: The surface mass balance of the Greenland ice sheet has decreased in recent decades with important implications for global sea level rise. Here a climate reanalysis model is used to examine observed circulation variability and changes in precipitation across southern Greenland to gain insight into the future climate in the region. The influence on precipitation from the North Atlantic Oscillation (NAO), Atlantic Multidecadal Oscillation (AMO), Icelandic Low, Azores High, regional blocking patterns, and near‐surface temperature and winds are explored. Statistically significant correlations are higher between precipitation and the Icelandic Low and near‐surface winds (0.5–0.7; p < 0.05) than correlations between precipitation and either the NAO or AMO climate indices (southwest Greenland: r = 0.12 and 0.28, respectively; and southeast Greenland: r = 0.25 and −0.07, respectively). Moreover, the recent enhanced warming in the Arctic (Arctic amplification) and the increase in the Greenland Blocking Index coincide with increased mean annual precipitation and interannual variability in southwest Greenland. Key Points: Southern Greenland precipitation is largely driven by topography and wind direction Recent enhanced increase of Arctic temperature linked with increase of southwest Greenland precipitation Positive feedback mechanisms in Arctic amplification linked with increase in southwest Greenland precipitation